Spongiform leukoencephalopathy in an adult mixed breed female dog - García, Juan A.; Batlle, Martí P.; Romero, Agustín; Alvarez, Eduardo; Dutra, Fernando (Brazilian Journal of Veterinary Pathology, 2020)
Leukoencephalomyelopathy is a nonspecific lesion characterized by widespread vacuolation of central nervous system white matter. It is mainly of genetic basis, occurring in young pure breed dogs. This report describes a neurodegenerative disease associated to demyelination in an adult mixed breed female dog. After 20 days in a kennel with 12 other dogs, the dog showed progressive nervous signs with ataxia and inability to maintain balance. No other dog was affected. After 15 days, the animal was euthanized in extremis and necropsied. No macroscopic lesions of diagnostic relevance were present. Microscopically, status espongiosus was observed in white matter throughout the length of the neuroaxis, from frontal brain lobe to lumbar spinal cord. Specific stains of Kluver Barrera and immunohistochemistry for the detection of phosphorylated and non-phosphorylated neurofilaments, microglia, astrocytosis, oligodendrocytosis and myelin proteins in brain and spinal cord sections showed demyelination, axonal fragmentation and degeneration, microgliosis and decrease of oligodendrocytes. The anatomopathological study and epidemiological data suggests a primary demyelination due to decrease in number and function of oligodendrocytes, which is probably of genetic basis with late onset.